Prismatic Effects in Bicentric Grinding - Remole, Arnulf (Canadian Journal of Optometry, 1981)
Bicentric grinding is widely used to neutralize a vertical differential prismatic effect at the near visual point. However, the prismatic effects in other portions of the reading field differ from those at the near visual point. In this study, the variations in prismatic effect throughout the entire reading field are demonstrated. It is shown that a slab-off prism is most effective in spherical anisometropic prescriptions and when the differential prismatic effects are symmetrical about the horizontal meridian.